Deletion of the α2A/α2C-adrenoceptors accelerates cutaneous wound healing in mice - Romana-Souza, Bruna; Nascimento, Adriana P.; Brum, Patricia C.; Monte-Alto-Costa, Andréa (International journal of experimental pathology, 2014)
Summary The α2‐adrenoceptors regulate the sympathetic nervous system, controlling presynaptic catecholamine release. However, the role of the α2‐adrenoceptors in cutaneous wound healing is poorly understood. Mice lacking both the α2A/α2C‐adrenoceptors were used to evaluate the participation of the α2‐adrenoceptor during cutaneous wound healing. A full‐thickness excisional lesion was performed on the dorsal skin of the α2A/α2C‐adrenoceptor knockout and wild‐type mice. Seven or fourteen days later, the animals were euthanized and the lesions were formalin‐fixed and paraffin‐embedded or frozen. Murine skin fibroblasts were also isolated from α2A/α2C‐adrenoceptor knockout and wild‐type mice, and fibroblast activity was evaluated. The in vivo study demonstrated that α2A/α2C‐adrenoceptor depletion accelerated wound contraction and re‐epithelialization. A reduction in the number of neutrophils and macrophages was observed in the α2A/α2C‐adrenoceptor knockout mice compared with wild‐type mice. In addition, α2A/α2C‐adrenoceptor depletion enhanced the levels of nitrite and hydroxyproline, and the protein expression of transforming growth factor‐β and vascular endothelial growth factor. Furthermore, α2A/α2C‐adrenoceptor depletion accelerated blood vessel formation and myofibroblast differentiation. The in vitro study demonstrated that skin fibroblasts isolated from α2A/α2C‐adrenoceptor knockout mice exhibited enhanced cell migration, α‐smooth muscle actin _protein expression and collagen deposition compared with wild‐type skin fibroblasts. In conclusion, α2A/α2C‐adrenoceptor deletion accelerates cutaneous wound healing in mice.